"Reap what you have not sown" Indigenous Knowledge Systems and Intellectual Property Laws in South Africa - George Sombe Mukuka (Pretoria University Law Press (PULP), 2010)
About the publication The aim of this book is to analyse the current status of indigenous intellectual property rights protection in South Africa. The current intellectual property laws and legislations in South Africa do not fully protect indigenous knowledge systems and in some instances the indigenous knowledge is misappropriated, abused without proper recognition and acknowledgement of the custodian of this knowledge. The book suggests that in order for us to fully understand the developments of intellectual property in South Africa, we need to look at similar developments in the United States and Australia. Using conceptual tools dealing with post-colonial, contested culture and legal theories such as the natural-law and the economic model, the book tries to analyse the current predicament: how can one possibly marry indigenous property rights and the western legal frameworks in a practical and ethical way? About the editor: George Sombe Mukuka holds two PhD degrees; in History from the University of KwaZulu-Natal and in Archaeology from the University of the Witwatersrand.